1988
DOI: 10.1103/physreva.37.470
|View full text |Cite
|
Sign up to set email alerts
|

Bidirectional ring laser: Stability analysis and time-dependent solutions

Abstract: %e provide a comprehensive analysis of the standard model of the bidirectional ring laser in which only one mode can be supported in each direction and in the limit that the polarization can be eliminated adiabatically. The interaction between the two counterpropagating modes can be derived and it is most naturally viewed as s coupling between them vis scattering from a spatial grating formed in the population inversion. If the grating is s sufficiently small modulation of the spatial average of the population… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
65
0

Year Published

1990
1990
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(70 citation statements)
references
References 56 publications
5
65
0
Order By: Relevance
“…An in-depth understanding of the mode-hopping in SRLs would shed light on the stochastic properties of the large class of Z 2 -symmetric systems. In spite of its importance, the problem of spontaneous directional switches in SRLs remains unaddressed, partly due to the high dimensionality of the models that have been proposed for SRLs [9,13].In this paper, we address the problem of such fluctuations both theoretically and experimentally. We experimentally investigate the properties of the residence time distribution (RTD) that quantifies the mode hopping.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…An in-depth understanding of the mode-hopping in SRLs would shed light on the stochastic properties of the large class of Z 2 -symmetric systems. In spite of its importance, the problem of spontaneous directional switches in SRLs remains unaddressed, partly due to the high dimensionality of the models that have been proposed for SRLs [9,13].In this paper, we address the problem of such fluctuations both theoretically and experimentally. We experimentally investigate the properties of the residence time distribution (RTD) that quantifies the mode hopping.…”
mentioning
confidence: 99%
“…An in-depth understanding of the mode-hopping in SRLs would shed light on the stochastic properties of the large class of Z 2 -symmetric systems. In spite of its importance, the problem of spontaneous directional switches in SRLs remains unaddressed, partly due to the high dimensionality of the models that have been proposed for SRLs [9,13].…”
mentioning
confidence: 99%
“…(16), and which we have observed are always the only stable modes] turn out to have C n symmetry as opposed to C nv symmetry, leading to spontaneous breaking of mirror symmetry as soon as the mode starts lasing (the only exception to this rule is for a C ∞v system, in which the circulating lasing modes have an intensity pattern |E| 2 ∝ |e i φ | 2 = 1, and hence still have mirror symmetry). We have also observed that circulating lasing modes in lossy C nv -symmetric cavities (such as that in Fig.…”
Section: Effects Of Chiralitymentioning
confidence: 98%
“…The literature on degenerate lasing modes has almost invariably dealt with whispering-gallery modes in microdisks and ring resonators [1][2][3][4]. Many of these earlier works discussed the stability of traveling-wave modes in ring resonators under perturbations that break the symmetry [15][16][17][18][19]. A very limited number of other works on degenerate lasing modes in other geometries exist [27], which were mostly experimental and focused on the linear cavity rather than the nonlinear lasing regime.…”
Section: B Effects Of Exact Degeneraciesmentioning
confidence: 99%
“…spectral hole burning effects. Self-and cross-saturation effects are added phenomenologically and are modeled by s and c. Contrary to the case of solid-state lasers [10], in the devices under study, the standing-wave pattern has a spatial period much smaller than the carrier diffusion length. Therefore, longitudinal variations of the carrier density will be washed out by the diffusion.…”
Section: Modelmentioning
confidence: 99%